A New Sonographic Weight Estimation Formula for Small‐for‐Gestational‐Age Fetuses. (27th June 2016) - Faschingbauer, Florian; Dammer, Ulf; Raabe, Eva; Kehl, Sven; Schmid, Matthias; Schild, Ralf L.; Beckmann, Matthias W.; Mayr, Andreas
Abstract : Objectives: The purpose of this study was to develop a new specific weight estimation formula for small‐for‐gestational‐age (SGA) fetuses that differentiated between symmetric and asymmetric growth patterns. Methods: A statistical estimation technique known as component‐wise gradient boosting was applied to a group of 898 SGA fetuses (symmetric, n = 750; asymmetric, n = 148). A new formula was derived from the data obtained and was then compared to other commonly used equations. Results: The new formula derived is as follows: estimated fetal weight = e^[1.3734627 + 0.0057133 × biparietal diameter + 0.0011282 × head circumference + 0.0201147 × abdominal circumference + 0.0183081 × femur length − 0.0000177 × biparietal diameter 2 − 0.0000018 × head circumference 2 − 0.0000297 × abdominal circumference 2 −0.0001007 × femur length 2 + 0.0397563 × I (sex = male) + 0.0064505 × gestational age (days) + 0.0096528 × I (SGA = asymmetric)], where the function I denotes an indicator function, which is 1 if the expression is fulfilled (sex = male; SGA type = asymmetric) and otherwise 0. In the whole study group and the 2 subgroups, the new formula showed the lowest median absolute percentage error, mean percentage error, and random error and the best distribution of absolute percentage errors within prespecified error bounds. Conclusions: The new formula substantially improves weight estimation in SGA fetuses.